2013
DOI: 10.1099/jmm.0.057216-0
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of carbapenem-resistant Acinetobacter baumannii in patients with diabetes mellitus in Saudi Arabia

Abstract: Carbapenem-resistant Acinetobacter baumannii is becoming increasingly prevalent in patients with diabetes mellitus in the Middle East. We examined the relationship of these bacteria and their resistance mechanisms to the diabetic disease status of patients in Saudi Arabia. Susceptibilities of 271 isolates to carbapenems, tigecycline and colistin were determined, followed by detection of carbapenemase genes. A bla VIM gene was detected in~95 % of isolates; bla OXA-23 and bla OXA-40 genes were also prevalent. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 20 publications
2
39
3
Order By: Relevance
“…The VIM enzyme is by far the most the predominant metallo-␤-lactamase to be detected in as many as 95% (254/271) of carbapenem resistant A. baumannii the isolates from Saudi Arabia (Alsultan et al, 2013) but this was not observed in our study as only 2 isolates were positive for bla VIM-2 carbapenemase.…”
Section: Isolatecontrasting
confidence: 80%
See 1 more Smart Citation
“…The VIM enzyme is by far the most the predominant metallo-␤-lactamase to be detected in as many as 95% (254/271) of carbapenem resistant A. baumannii the isolates from Saudi Arabia (Alsultan et al, 2013) but this was not observed in our study as only 2 isolates were positive for bla VIM-2 carbapenemase.…”
Section: Isolatecontrasting
confidence: 80%
“…There have been reports of CRAB in patients with diabetes mellitus in Saudi Arabia. They have become a serious problem in immunocompromised patients and the scenario is particularly worrying in Middle-Eastern countries due to the increasing number of infections that are difficult to treat (Alsultan et al, 2009(Alsultan et al, , 2013. The aim of this study was to characterise and understand the molecular epidemiology of clinical isolates of A. baumannii from two medical centres in Saudi Arabia and two from Egypt, collected in 2013 and 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Alsultan et al (2013) are unusual by international standards, where the most frequent carbapenem-hydrolysing b-lactamases in A. baumannii are oxacillinases (OXA-23, OXA-40, OXA-58 and OXA-143) (Nordmann, 2010). Many reports from the Kingdom confirmed the prevalence of oxacillinases (particularly OXA-23) among carbapenem-resistant A. baumannii.…”
Section: A Baumanniimentioning
confidence: 65%
“…In a recent multicentre study including 37 Saudi hospitals, Alsultan et al (2013) investigated the molecular basis of resistance in 196 carbapenem-resistant A. baumannii isolated between 2008 and 2011. A high proportion of isolates (99 %) carried genes for at least one acquired carbapenem-hydrolysing b-lactamase.…”
Section: A Baumanniimentioning
confidence: 99%
“…The studies have indicated that carbapenems resistance among Gram negative bacteria has become a global issue [13]. Recent studies showed that Saudi Arabia is considered among the countries that reported high rates of antimicrobial resistance [14] [15]. Thus, this study aimed to detect the prevalence of carbapenem resistance among Gram negative bacteria at the Al-Noor Specialist Hospital in the western part of Saudi Arabia, and monitoring to carbapenem resistance among these types of bacteria in order to devise strategies to counter threats from these extremely dangerous bacteria.…”
Section: Introductionmentioning
confidence: 99%